Freedom seekers : escaping from slavery in restoration london - Newman, Simon P. (Simon Peter), 1960- (Institute of Historical Research, 2022)
Freedom Seekers: Escaping from Slavery in Restoration London by Simon Newman reveals the hidden stories of enslaved people who attempted to escape from captivity in England's capital during the 17th century. Using newspaper advertisements, maps, and other sources, Newman reconstructs the lives of these freedom seekers, their escape routes, and the networks of support they relied on. The book demonstrates that racial slavery was not just a colonial phenomenon, but was also present and practiced in England itself. It also highlights the resilience and courage of enslaved people who resisted their bondage and fought for their freedom.